Overcoming poverty multi-disciplinary perspectives, principles and practices - Aldaba, Fernando T.; Cristobal, Fortunato L.; Lopez, Mario A. G.,V; Mendoza, Ronald U.; Ortigas, Carmela D.; Racelis, Mary (C & E Publishing, Inc., 2016)
"Poverty remains a persistent problem in the Philippines despite episodes of economic growth. More recently, the country has been experiencing a higher level of economic expansion not seen in recent years, with annual gross domestic product growing at more than 6%. Unfortunately, poverty incidence, the proportion of the poor over the total population, has remained at the 20% level over the last few years. Official government statistics cannot deny this. In this book, a diverse group composed of two economists, a medical doctor, a development manager, a psychologist, and a social anthropologist brings out the multi-dimensional character of poverty. They provide clarity to principles and ways for more effective coordination and multi-stakeholder action. This book was written especially for NGOs and faith-based development workers, government personnel in anti-poverty work, private sector corporate social responsibility advocates, and the general public interested in understanding poverty and well-being issues and, possibly, how they themselves can sharpen their approaches to addressing and overcoming poverty"--Cover.